2016
DOI: 10.1186/s12953-017-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiles of hatchery egg shell membrane

Abstract: BackgroundEggshells which consist largely of calcareous outer shell and shell membranes, constitute a significant part of poultry hatchery waste. The shell membranes (ESM) not only contain proteins that originate from egg whites but also from the developing embryos and different contaminants of microbial and environmental origins. As feed supplements, during post hatch growth, the hatchery egg shell membranes (HESM) have shown potential for imparting resistance of chickens to endotoxin stress and exert positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…The oviduct is divided into 5 parts: infundibulum, magnum, isthmus, uterus, and vagina, and each has distinctive roles in egg formation and production. Several hormones, proteins, and genes have been identified in the oviduct to regulate the processes and functions of the oviduct in egg formation and production ( Brionne et al, 2014 ; Hrabia et al, 2014 ; Atikuzzaman et al, 2015 ; Du et al, 2015 ; Zhao et al, 2016 ; Rath et al, 2017 ; Socha et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The oviduct is divided into 5 parts: infundibulum, magnum, isthmus, uterus, and vagina, and each has distinctive roles in egg formation and production. Several hormones, proteins, and genes have been identified in the oviduct to regulate the processes and functions of the oviduct in egg formation and production ( Brionne et al, 2014 ; Hrabia et al, 2014 ; Atikuzzaman et al, 2015 ; Du et al, 2015 ; Zhao et al, 2016 ; Rath et al, 2017 ; Socha et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…They may also render discarded material from agroindustrial and cosmetological preparations a valuable source of physiologically active molecules for a possible use as nutraceuticals. Combined electrophoretic and mass spectrometric approaches have been successfully used to describe the protein repertoire of different hen egg compartments. These studies demonstrated the occurrence of distinct protein components in yolk plasma and granules . Whether the first one contains water-soluble α-livetin (serum albumin), β-livetin (α2-glycoprotein), and γ-livetin, the latter are characterized for the presence of lipovitellins as components of high-density lipoprotein, phosvitin, and low-density lipoprotein apolipoproteins, which are synthesized in the liver, transported into the oocyte, and then processed in yolk to yield mature proteins. ,, …”
Section: Introductionmentioning
confidence: 99%
“…ESM has emerged as an efficient feed supplement to post-hatchery chicks to improve immunity and egg-laying performance ( Makkar et al, 2015 ). The protection of embryos upon treatment with ESM is attributed to the antimicrobial nature of lysozyme, keratin peptides, ovocalyxin, ovotransferrin, ovalbumin Y, ovostatin, ovomucoid, and ovoglycan, since a bacterial LPS-induced inflammatory response and a reduced level of stress markers such as plasma corticosterone levels were transferred to feed chicks ( Rath et al, 2016 ). ES powder, a rich source of calcium, can improve the laying performance of birds ( Cordeiro and Hincke, 2011 ).…”
Section: Role Of Egg Components In Veterinary Medicinementioning
confidence: 99%